Wasting, underweight and stunting among children with congenital heart disease presenting at Mulago hospital, Uganda. Issue 1 (December 2017) - Batte, Anthony; Lwabi, Peter; Lubega, Sulaiman; Kiguli, Sarah; Otwombe, Kennedy; Chimoyi, Lucy; Nabatte, Violette; Karamagi, Charles
Abstract Background Children with congenital heart disease are at increased risk of malnutrition. The aim of this study was to describe the prevalence of wasting, underweight and stunting among children with congenital heart disease attending Mulago National Referral Hospital, Uganda. Methods A cross-sectional study among 194 children aged 0–15 years was conducted between August 2013 and March 2014. Anthropometric measurements and clinical assessments were carried out on all children. Anthropometric z-scores based on WHO 2007 reference ranges were generated for each child. Weight-for-height z-scores were generated for children 0–5 years, weight-for-age z-scores for children 0–10 years, and height-for-age and BMI-for-age z-scores for all children. Risk factors associated with malnutrition were determined by Poisson regression. Results One hundred and forty five (74.7%) children were aged 0–5 years; and 111 of 194 (57.2%) were female. Forty five of 145 (31.5%) children aged 0–5 years were wasted; 77 of 181 (42.5%) children aged 0–10 years were underweight; 88 of 194 (45.4%) children were stunted; and 53 of 194 (27.3%) children were thin (BMI for age z score < −2). Moderate to severe anaemia (RR 1.11, 95% CI: 1.01–1.22) and moderate to severe heart failure (RR 1.24, 95% CI: 1.13–1.36) were associated with wasting and underweight respectively. Stunting was associated with moderate to severe heart failure (RR 1.11, 95% CI: 1.01–1.21) while thinness was associated with moderate to severe heart failure (RR 1.12, 95% CI: 1.04–1.21) and moderate to severe anaemia (RR 1.15, 95% CI: 1.06–1.25). Conclusion Malnutrition is common in children with congenital heart disease, and is associated with anaemia and heart failure. There is need to integrate strategies to identify and manage malnutrition during the care of children with congenital heart disease.